A study on the applicability of Si in low-Mo duplex stainless steel weld metals to improve the corrosion resistance. (February 2015) - Kim, Sung Jin; Kim, Jeong Kil; Park, Sang-Hong
Abstract :  The applicability of Si in low-Mo duplex stainless steel weld metals is examined in terms of corrosion resistance and impact toughness. Nano-secondary ion mass spectrometry and three-dimensional atom probe analysis indicate that Si is enriched at the outermost layer in the form of Si-oxide a few nanometer thick, leading to a significant increase in critical pitting temperature without sacrificing the impact toughness. Improved corrosion resistance suggests that the thin oxide layer possibly acts as a diffusion barrier against aggressive ionic species.